2018
DOI: 10.1002/cctc.201701408
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Bacterial Members of the Imine Reductase Enzyme Family that Perform Reductive Amination

Abstract: Reductive amination of carbonyl compounds constitutes one of the most efficient ways to rapidly construct chiral and achiral amine frameworks. Imine reductase (IRED) biocatalysts represent a versatile family of enzymes for amine synthesis through NADPH‐mediated imine reduction. The reductive aminases (RedAms) are a subfamily of IREDs that were recently shown to catalyze imine formation as well as imine reduction. Herein, a diverse library of novel enzymes were expressed and screened as cell‐free lysates for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
104
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(106 citation statements)
references
References 37 publications
0
104
0
Order By: Relevance
“…The preferred cofactor is generally NADPH, but it has been shown that structure‐guided protein engineering can be used to increase the specific activity of IREDs towards the non‐phosphorylated nicotinamide cofactor (NADH) . Moreover, it has been found that IREDs are not limited to reducing cyclic imines but that they are also capable of coupling carbonyl compounds and amines in a reductive amination reaction, albeit at often drastically reduced rates . While most IREDs seem to rely on spontaneous imine formation from the amine and carbonyl substrates when performing such reductive aminations, a sub‐class of the IRED family, termed ‘reductive aminases’, has been found capable of catalysing the imine formation step as well .…”
Section: Introductionmentioning
confidence: 99%
“…The preferred cofactor is generally NADPH, but it has been shown that structure‐guided protein engineering can be used to increase the specific activity of IREDs towards the non‐phosphorylated nicotinamide cofactor (NADH) . Moreover, it has been found that IREDs are not limited to reducing cyclic imines but that they are also capable of coupling carbonyl compounds and amines in a reductive amination reaction, albeit at often drastically reduced rates . While most IREDs seem to rely on spontaneous imine formation from the amine and carbonyl substrates when performing such reductive aminations, a sub‐class of the IRED family, termed ‘reductive aminases’, has been found capable of catalysing the imine formation step as well .…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] When presented with ketones, such as acetophenone, and a large excess of ammonia or other amine, these NADPH-dependent enzymes catalyze the asymmetric reduction of imines formed in solution, to give chiral amine products such as α-methylbenzylamine (3 b) in a theoretically quantitative yield and with high enantiomeric excess (Scheme 2). A subgroup of IRED enzymes, reductive aminases (RedAms) [16][17][18] has also been shown to catalyze the formation of the iminium ion with certain ketone and amine partners, with the consequence that the coupling [a] D.…”
mentioning
confidence: 99%
“…[14,15] When presented with ketones, such as acetophenone, and a large excess of ammonia or other amine, these NADPH-dependent enzymes catalyze the asymmetric reduction of imines formed in solution, to give chiral amine products such as α-methylbenzylamine (3 b) in a theoretically quantitative yield and with high enantiomeric excess (Scheme 2). A subgroup of IRED enzymes, reductive aminases (RedAms) [16][17][18] has also been shown to catalyze the formation of the iminium ion with certain ketone and amine partners, with the consequence that the coupling reaction is achieved with the supply of only an equimolar ratio of the substrates. [16,19] Interestingly, when presented with α,α,αtrifluoroacetophenone 5 a (Scheme 2), a promiscuous reduction of the ketone to the alcohol 5 e is performed by an IRED from Streptosporangium roseum (SrIRED), [20] a reaction which has thus far not been observed in any other IRED/RedAm-catalyzed transformation of any carbonyl substrate.…”
mentioning
confidence: 99%
“…Another fairly recent development is the emergence of imine reductases (IREDs) [114][115][116][117][118][119] for the enantioselective reduction of cyclic imines derived from secondary amines and the asymmetric reductive amination of ketones with primary amines (Scheme 7). [120][121][122][123] The concept of chiral amine synthesis via enzymatic reductive amination was taken to a new level of sophistication by applying the concept of hydrogen borrowing (itself having been borrowed from the chemocatalytic literature).…”
Section: Redox Processesmentioning
confidence: 99%